Single‐Molecule Study of Peptides with the Same Amino Acid Composition but Different Sequences by Using an Aerolysin Nanopore. (13th May 2020) - Hu, Fangzhou; Angelov, Borislav; Li, Shuang; Li, Na; Lin, Xubo; Zou, Aihua
Abstract: Nanopores are original sensors employed for highly sensitive peptides/proteins detection. Herein, we describe the use of an aerolysin nanopore to identify two similar model peptides, YEQYEQQDDDRQQQ (YEQ2Q3) and QDDDRQQQYEQYEQ (Q3YEQ2), with the same amino acid composition but different sequences. All‐atom molecular dynamics (MD) simulations reveal that YEQ2Q3 possesses fewer hydrogen bonds and a more extended conformation than Q3YEQ2. These two peptides, which fold differently, exhibit obviously distinct mass‐independent current blockades with characteristic dwell times when entering the aerolysin nanopore. Typically, at +60 mV, the statistical dwell time of 0.630±0.018 ms for peptide Q3YEQ2 is four times longer than the value of 0.160±0.001 ms for peptide YEQ2Q3, and yet peptide YEQ2Q3 induces ∼1.9 % larger blockade current amplitude than peptide Q3YEQ2. The obtained results show the remarkable potential of aerolysin nanopore for peptides/proteins identification, characterization, sequencing and also demonstrate that the mass identification of nonuniformly charged peptides/proteins by using the nanopore technique could be complicated by their folded structure and complex analyte‐pore interaction. Abstract : Dwelling pace : Two model peptides YEQYEQQDDDRQQQ and QDDDRQQQYEQYEQ were investigated at the single‐molecule level. The relative distances between negatively charged residues D and E and between polar residues Q and Y are different, thus the peptides have different intramolecular interactions and structures. When they enter a single aerolysin nanopore, they induce distinct current blockades with characteristic dwell times.